Interpretation of the pathogenesis and therapeutic mechanisms of first-episode major depressive disorder based on multiple amino acid metabolic pathways: a metabolomics study - Guo, Zhihao; Zhang, Zi; Huang, Wanting; Xia, Hui; Huang, Shanqing; Lan, Xiaofeng; Ning, Yuping; Zhou, Yanling; Shang, Dewei (Metabolic brain disease, 2024)
Objectives: Given the unclear etiology and treatment mechanisms of depression, we aim to explore the metabolic differences between patients with major depressive disorder (MDD) and the healthy population, as well as before and after treatment with escitalopram (ESC). Methods: Recruit first-episode drug-naïve MDD (DN-MDD) patients and healthy controls (HCs). Clinical data and serum samples from all subjects were collected at baseline and patients’ samples were collected again after ESC monotherapy for four weeks. Perform non-targeted metabolomic analysis and apply MetaboAnalyst 5.0 to identify differential metabolites and execute KEGG pathway enrichment. Results: Through metabolomic analysis of serum samples, 904 differential metabolites were identified in the DN-MDD group compared to the HCs, and 455 metabolites in treated patients compared to DN-MDD patients. In the pathway analysis, DN-MDD state regulated functions of histidine, beta-alanine, aspartate, and tryptophan metabolism, while ESC treatment produced an influence on the biological process of aspartate and sphingolipid. Conclusion: We respectively depicted metabolism-related biomolecular changes in the serum of patients suffering from MDD and undergoing ESC treatment. Multiple amino acid metabolism pathways were adjusted in MDD patients, and levels of aspartate, arginine and sphingolipids were regulated after ESC monotherapy. These biomolecular changes may bring new insights into the biology and treatment of MDD from the perspective of the serum metabolites.